2022
DOI: 10.3390/insects13060536
|View full text |Cite
|
Sign up to set email alerts
|

Differential Hatching, Development, Oviposition, and Longevity Patterns among Colombian Aedes aegypti Populations

Abstract: Dengue, Zika, and chikungunya are arboviral diseases for which there are no effective therapies or vaccines. The only way to avoid their transmission is by controlling the vector Aedes aegypti, but insecticide resistance limits this strategy. To generate relevant information for surveillance and control mechanisms, we determined life cycle parameters, including longevity, fecundity, and mortality, of Colombian Ae. aegypti populations from four different geographical regions: Neiva, Bello, Itagüí, and Riohacha.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 111 publications
0
16
0
Order By: Relevance
“…The life cycle of an Ae. aegypti mosquito from egg to adult can take between 7 to 10 days depending on temperature and mosquito strain [ 49 ]. Residual cypermethrin killing or expelling some of newly emerged and imported adults from unsprayed areas, as well as reduced egg-laying due to the decreased number of adults, could further explain the delayed recovery of the adult mosquito population [ 22 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The life cycle of an Ae. aegypti mosquito from egg to adult can take between 7 to 10 days depending on temperature and mosquito strain [ 49 ]. Residual cypermethrin killing or expelling some of newly emerged and imported adults from unsprayed areas, as well as reduced egg-laying due to the decreased number of adults, could further explain the delayed recovery of the adult mosquito population [ 22 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, it has been shown that even in geographically close populations there may be differences for Ae. aegypti in vector competence for DENV [ 54 , 55 ] and in hatching, development time, longevity, and fecundity [ 56 ]. This suggests that some specific parameters at the local level, such as bacterial diversity or resistance to insecticides, may be differential and relevant to elucidate the different degrees of transmission of arboviruses.…”
Section: Methodsmentioning
confidence: 99%
“…Egg production from each female may vary. In the field, each female can lay between 20-60 eggs, but in the insectary, it can reach up to 100-150 eggs (Clemons et al 2010;Arévalo-Cortés et al 2022). Based on our data, each female can produce approximately 70 eggs in the first gonotrophic cycle (GC1), and it will drop in the 3 rd gonotrophic cycle (GC3) to up to 50 eggs (unpublished result).…”
Section: Ratio Of Female and Malementioning
confidence: 99%
“…aegypti has a strong interest in human blood. Due to this reason and the quality of the eggs, we allowed one-week-old adult colony to be blood -fed by human volunteers once a week (Gunathilaka et al 2017;Al-Rashidi et al 2022;Arévalo-Cortés et al 2022). One cage was only blood fed by one person.…”
Section: Egg Harvesting and Production Capacitymentioning
confidence: 99%